Improving Critical Thinking Skill Through Team-based Projects, is it Effective? - Aristin, Nevy Farista; Purnomo, Agus (LPPM Undiksha, 2022)
Facing the 21st-century learning era, critical thinking skills are very important for students and become one of the goals of education in higher education. To achieve one of these educational goals, learning is needed that can form critical, innovative, creative, and competitive students. This study aims to improve students' critical thinking skills on materials for developing rural and urban areas in a sustainable manner in wetlands, through a team-based project learning model. This research uses a pre-experimental design with one group pretest-posttest. The sample used was 47 students, formed into 11 groups. The team-based project model is carried out in six steps, namely 1) initial orientation, 2) identification of problems (cases), 3) project planning, 4) project implementation, 5) presenting project results, and 6) evaluating project results. Data processing was carried out using pretest and posttest, normality test (Shapiro Wilk), and homogeneity test (Lavene test) and analyzed using a paired sample t-test. The results of the study stated that there are differences in learning outcomes after using the team-based project model in improving students' critical thinking skills in rural and urban areas in a sustainable manner in wetlands. This is because students can integrate theory and practicum by producing products through projects in the form of articles in national journals. So, it can be implied in the learning of each subject, both theory-based and practical, to improve students' critical thinking skills.